The Evening and the Morning - Follett, Ken. ([S.l.]: Penguin Random House, 2020)
From the #1 New York Times bestselling author, a thrilling and addictive new novel--a prequel to The Pillars of the Earth--set in England at the dawn of a new era: the Middle Ages "Just as transporting as [The Pillars of the Earth] . . . A most welcome addition to the Kingsbridge series." --The Washington Post It is 997 CE, the end of the Dark Ages. England is facing attacks from the Welsh in the west and the Vikings in the east. Those in power bend justice according to their will, regardless of ordinary people and often in conflict with ...
Read by John Lee.
Keywords: Suspense -- Thrillers